Developing company competitiveness based on entrepreneurial values, transformational leadership, and service innovation through organizational performance - Solikin Solikin; Muhammad Thamrin; Suharto Abdul Majid; Librita Arifiani (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Company competitiveness is very important for business continuity. Therefore, the research aims to investigate and find an empirical model of the influence of entrepreneurial values, transformational leadership, and service innovation on company competitiveness through mediating mechanisms of organizational performance. The research uses a quantitative approach with survey methods and causal design. The sample was 153 leaders of ferry companies in Indonesia.The research instruments consist of organizational performance, competitiveness, entrepreneurial values, transformational leadership, and service innovation, as questionnaires were designed as a Likert scale. The questionnaire was distributed in Google Form format via the WhatsApp application. Data were analyzed using structural equation modeling analysis based on partial least squares (SEM-PLS). The research's findings demonstrate that entrepreneurial values, transformational leadership, service innovation, and organizational performance all significantly impact a company's competitiveness; additionally, entrepreneurial values, transformational leadership, and service innovation have a major impact on organizational performance, which in turn has a significant impact on company competitiveness. These results support a novel empirical model of how entrepreneurial values, transformational leadership, and service innovation affect company competitivenessby using organizational performance as a mediating factor. Before being modified or used for their future work, researchers, academics, and practitioners should critically examine this new model without discounting some of the study's limitations.